Efikasi Diri dan Pengambilan Keputusan Karir Siswa Kelas XII SMAN 1 Tilatang Kamang Kabupaten Agam - Murisal Murisal; Erna Dewita; Fadil Maiseptian; Sari Dewi Kurnia Oktafia (Jurnal Pendidikan dan Konseling (JPDK), 2022)
This study examines the self-efficacy and career choices of students in Class XII, SMAN 1 Tilatang Kamang. The results of the fieldwork indicated that many students were still hesitant to make a professional decision after leaving school. Students who were reluctant to make career decisions meant those students had lower self-efficacy. The purpose of this study was to determine students' self-efficacy and career decision-making. The type of study was a related quantitative study using the Self-Efficacy Scale and the Career Decision Scale. The study was conducted with 30 students. The self-efficacy scale, on the other hand, had a reliability of 0.932 in making career decisions, with 46 valid items out of 84 tested. The results of the study of 65 students from the analysis test conducted by SPSS for Windows 20.0 showed that there was no association between self-efficacy and career choice, and the correlation coefficient value was -0.189, which was negative. It can be concluded that there is no relationship between self-efficacy and career decision-making in students, with a very low level of closeness. The level of career decision-making has a high level of 64 students or 98.46% and the level of self-efficacy in choosing a study program is 34 or 52.31%.